Analysis of narratives about development: “Food safety” and “Food sovereignty” in Colombia and Bolivia - Nova-Laverde, Mariluz; Rojas-Chávez, Mariana; Ramírez-Vanegas, Yuly Viviana (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
This paper analyzes, from a post-structuralist epistemological approach, the discourses on "development" included in the national policy of "Food Security" and those on "Food Sovereignty" promulgated by the peasant, ethical and popular social movements in Colombia. For this, the methodology of public policy narrative analysis is used and it is concluded that the concept of "Food Security", that constitutes the official narrative of the Colombian Government to attack the problems of malnutrition and famine, understands development mainly as economic growth, an objective that is pursued by increasing agricultural productivity with genetic modifications, large-scale production, the reduction of trade barriers and the transfer of technology while the discursive logic of "Food Sovereignty", proclaimed by subaltern groups, advocates the inclusion of ancestral knowledge in agro ecology, short production and distribution circuits, the defense of the territory, the protection of nature and the protection of life, concepts related to the alternatives to "development". Finally, as a meta-narrative, the case of rural policies and the eradication of hunger in Bolivia is reviewed, which present food security and sovereignty as complementary objectives and illustrate the strategies of transition towards a “Living Well" model.